Новые данные об изменчивости ветра в северо-западной части Черного моря - Полонский, А.Б.; Гармашов, А.В. (Доповіді НАН України, 2010)
На пiдставi аналiзу даних тривалих iнструментальних спостережень за вiтром, виконаних на стацiонарнiй газодобувнiй платформi в Каркинiтськiй затоцi, видiлено статистично значущi нестацiонарнi коливання модуля та складових вектора вiтру в iнтервалi перiодiв вiд 0,5 до 15 дiб. Виявлено значну перемiжнiсть не тiльки бризових (~ 1 доба) i синоптичних (~ 2–6 дiб), а й бiльш низькочастотних внутрiшньомiсячних флуктацiй швидкостi вiтру з типовими перiодами ~ 10–15 дiб. Їх максимальна амплiтуда приурочена до осiнньо-зимового сезону 1997/1998 рр., тобто вiдзначалась у зрiлу фазу одного з найiнтенсивнiших Ель-Нiньо за весь перiод iнструментальних спостережень. У цей час енергiя внутрiшньомiсячних низькочастотних флуктацiй швидкостi вiтру (~ 7 м²/с²) у 1,5 раза перевищувала енергiю коливань у синоптичнiй областi спектра. Цi результати пiдтверджуються аналiзом даних берегової гiдрометеорологiчної станцiї “Одеса-порт”, а також даних ре-аналiзу Японського метеорологiчного товариства. On the basis of the analysis of long-term instrumental observations of winds carried out on a stationary gas extraction platform in the Karkinitsky bay, the statistically significant non-stationary fluctuations of the modulus and components of the wind vector in the interval of periods (T) from 0.5 to 15 days are studied. The considerable alternation not only of breeze (T ~ 1 day) and synoptic (T ~ 2–6 days) fluctuations of the wind speed, but also intra-month ones with lower frequencies and typical periods ~ 10–15 days are marked. Their maximal amplitude was observed in the autumn-winter season of 1997/1998, i. e. in the mature phase of one of the most intense El-Nino during the whole period of instrumental measurements. At that time, the energy of intramonth low-frequency wind fluctuations (~ 7 m²/s²) exceeded the energy of fluctuations in the synoptic interval of the spectrum by 1.5 times. These results are confirmed by the analysis of data of the coastal hydrometeorological station “Odessa-port” and data f the re-analysis of the Japanese meteorological society.